THE CONCEPT OF A COMPREHENSIVE ANALYSIS OF STATUS AND TRENDS OF SOCIO-ECONOMIC AND FINANCIAL SYSTEM AT THE MESO-LEVEL - Aleksandr Milenkov (Вестник Северо-Кавказского федерального университета)
The relevance of the article is the fact that in the study ofprocesses of interaction of economic systems of different hierarchical levels should use objective data comprehensive analysis of the status and trends of development of conceptual provisions of which are currently not developed to the extent that allows its use in applied research. The article describes the author's suggestions for the formation of the concept of analysis of status and trends of development of the socio-economic sphere of the subject of Federation and a regionalfinancial system based on inter-tier approach assessing the impact of complex financial institutions on the development of he region. The concept includes the substantiation of composition and of determining the numerical value of the indicators characterizing socio-economic condition of a region as an endogenous variable for the parameters of the regional inancial system.